Differentiating between gestational and chronic hypertension; an explorative study. (21st January 2013) - Terwisscha van Scheltinga, Josien A.; Krabbendam, Ineke; Spaanderman, Marc E.A.
Abstract Objective Guidelines define hypertension diagnosed before 20 weeks' gestation as chronic hypertension (CH) and thereafter as gestational hypertension (GH). We tested whether hypertension diagnosed before 20 weeks is preceded by CH and whether pregnancy outcome depends on the time of onset of hypertension. Design Retrospective cohort study. Setting Tertiary obstetric center. Population Women with a history of obstetric vascular complications. Methods Blood pressure data prior to and during pregnancy and subsequent maternal and neonatal outcome were reviewed in 148 women. Women were grouped according to the onset of hypertension; pre‐pregnancy (CH), before 20 weeks' (early GH), after 20 weeks' gestation (late GH) and normotensive. Main outcome measures Onset of hypertension, obstetric complications (pre‐eclampsia, HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome, intra‐uterine growth restriction). Results Twenty‐nine women had CH. Early GH occurred in 46 women and another 32 developed late GH. Of 75 women with hypertension in the first half of pregnancy, 29 (39%) had CH and 46 (61%) early GH. Obstetric complications occurred more often in all hypertensive women, but no differences between the CH and GH groups could be detected. Conclusions Hypertension detected in the first half of pregnancy does not necessarily indicate chronic hypertension. Hypertension in general is related to hypertensive maternal complications and fetal growth restriction. Differentiating between chronic or gestational hypertension does not seem to help in establishing the risk for later hypertensive sequelae or intra‐uterine growth restriction.